PENILAIAN KEPUASAN KONSUMEN INTERNAL DI BIDANG JASA PENDIDIKAN (Studi Kasus di Fakultas Ekonomi dan Psikologi Universitas Muhammadiyah Surakarta) - Padmantyo, Sri; Haryanto, Haryanto; Imronuddin, Imronuddin (Universitas Muhammadiyah Surakarta, 2004)
Quality and customers are two important factors for every organization. Good quality is usuallyfollowed by customersâ loyality. Therefore, organization should enhance their quality improvement. Thisresearch is aimed at investigating internal customersâ satisfaction in education services. Two faculties inMuhammadiyah University of Surakarta are chosen as sample, i.e. Economics Faculty and PsychologyFaculty. The result shows that most of internal customers of the two faculties are less satisfied than it isshould be.